Laws of the Creek Nation - Deer, Sarah; Waring, Antonio (University of Georgia Press, 2023)
Laws of the Creek Nation is a transcript of the list of laws made by the Creek National Council. This list was compiled in 1825 by the clerk of council, Chilly McIntosh, for Georgia governor George Troup. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.